2011
DOI: 10.3155/1047-3289.61.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Windsor, Ontario Exposure Assessment Study: Design and Methods Validation of Personal, Indoor, and Outdoor Air Pollution Monitoring

Abstract: The Windsor, Ontario Exposure Assessment Study evaluated the contribution of ambient air pollutants to personal and indoor exposures of adults and asthmatic children living in Windsor, Ontario, Canada. In addition, the role of personal, indoor, and outdoor air pollution exposures upon asthmatic children's respiratory health was assessed. Several active and passive sampling methods were applied, or adapted, for personal, indoor, and outdoor residential monitoring of nitrogen dioxide, volatile Extensive quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The DustTraks were programmed to sample every minute. Research performed elsewhere reported that side‐by‐side sampling indicated that DustTrak was highly correlated with gravimetric instrument 24 . Prior to the measurements, the two DustTraks have been factory calibrated.…”
Section: Methodsmentioning
confidence: 99%
“…The DustTraks were programmed to sample every minute. Research performed elsewhere reported that side‐by‐side sampling indicated that DustTrak was highly correlated with gravimetric instrument 24 . Prior to the measurements, the two DustTraks have been factory calibrated.…”
Section: Methodsmentioning
confidence: 99%
“…In advancing our understanding of residential air exchange and its relationship with IAQ, we must assess the errors and biases in the methods by which we measure air exchange. Several studies of air exchange rates (AERs) have been undertaken in some thousands of homes (Dodson et al., ; Gilbert et al., , ; Heroux et al., ; Hun et al., ; Weisel et al., ; Wheeler et al., ). These studies have employed the commonly used tracer gas method which employs inert gases not found in nature [perfluorinated cyclic hydrocarbon tracers (PFTs)] to determine AERs (Dietz and Cote, ; Dietz et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Health Canada (HC), in collaboration with local universities, has conducted IAQ studies in several Canadian cities over the past 9 years (Clark et al., ; Heroux et al., ; MacNeill et al., ; Wheeler et al., ). Each study represented an extensive program of IAQ measurements and AER characterization using the perfluorocarbon tracer (PFT) single‐zone method.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis found an association between childhood leukemia and prenatal maternal occupational pesticide exposure [1,2]. Creation of a system that continuously collects, stores, and analyzes information about environmentally-induced diseases, exposure, and risk factors, as well as a timely dissemination of this information to the decision-makers is an important approach being undertaken in some regions [3][4][5]. The Policy Interpretation Network on Children's Health and Environment (PINCHE) was set up within EU FP5 (QLK4-2002-02395) to protect the health of children and provide a prioritized list of risk factors and policy recommendations for action [6].…”
Section: Introductionmentioning
confidence: 99%